Zur Internationalisierung von Schule und Hochschule - Graumann, Olga (International Dialogues on Education Journal, 2016)
Internationalization is more imporant than ever for today’s universities and schools. Up until into the 20th century, research exchanges beyond national boundaries were left to individual initiatives. Today the internationalization of schools and universities is carried out through funding programs which financially secure mobility and international research activites. Through concrete examples of international network creation, the article demonstrates how universities can fulfill the mandate of internationalization. Heterogeneity should drive innovation and development on all levels. Although schools have been faced with migration movements for decades, social diversity is still not recognized enough as a possibiliy for innovation. Nowadays, intercultural education must be central. The internationalization of schools and universities is situated between global, national and regional challenges. Internationalization per se is neither „good“ nor „bad“; however, whether it leads to „the good“, to more „humanitas“ and the ideal of of the „global citizen“, rests in the hands of those who are responsible for internationalization at the respective school or university.